2015
DOI: 10.1186/s12885-015-1662-6
|View full text |Cite
|
Sign up to set email alerts
|

c-MET immunostaining in colorectal carcinoma is associated with local disease recurrence

Abstract: BackgroundIncreased mesenchymal–epithelial transition factor gene (c-MET) expression in several human malignancies is related to increased tumour progression. The aim of the present study is to explore the relationship between immunohistochemical expression of c-MET in colorectal carcinoma (CRC) and the clinicopathological characteristics and follow up data, to compare the expression of c-MET in primary CRC and its metastasis in lymph nodes and to test its validity as independent prognostic factor.MethodsHundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 23 publications
(23 reference statements)
2
38
0
Order By: Relevance
“…Furthermore, CSC is known as a pivotal factor contributing to cancer relapse and metastasis. Studies that show c‐Met activation is associated with poor prognosis for survival and local disease recurrence supports our findings (Al‐Maghrabi et al, ; Lee et al, ). Our results show that celecoxib suppresses CSC property of CRC cells mainly through c‐Met inhibition.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, CSC is known as a pivotal factor contributing to cancer relapse and metastasis. Studies that show c‐Met activation is associated with poor prognosis for survival and local disease recurrence supports our findings (Al‐Maghrabi et al, ; Lee et al, ). Our results show that celecoxib suppresses CSC property of CRC cells mainly through c‐Met inhibition.…”
Section: Discussionsupporting
confidence: 91%
“…A growing body of evidence‐based research shows that c‐Met tyrosine kinase inhibitors can block c‐Met signaling and reverse tumor growth in different cancers . Recent studies have shown that MET signaling in lung cancer and gastric cancer is sensitive to inhibition using a specific tyrosine kinase inhibitor . These findings suggested that overexpressed c‐Met may act as an important biomarker for CRC targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[181920] Two cylindrical cores of 1.5 mm in diameter were selected from donor paraffin blocks and arrayed in recipient paraffin blocks using the automated tissue arrayer (Master 3D Histech). Normal placenta tissue was used as control tissue to help orientation of samples in each tissue microarray block.…”
Section: Methodsmentioning
confidence: 99%